Design and Simulation of Strained Si/SiGe HBT Architecture with Uniaxially-stressed Collector - Wen, Jianhao; Wei, Jinxi; Song, Qi; Wang, Guanyu; Zhou, Chunyu; Wang, Wei (2021 International Symposium on Devices, Circuits and Systems (ISDCS), 2021)
A novel SiGe HBT architecture is designed by introducing the embedded Si 1−y Ge y stress raiser into the collector. In the proposed HBT structure, the emission region, the base region and the collector region are all subjected to stress, so as to enhance the characteristic frequency. The effect of embedded Si 1−y Ge y stress raiser on the frequency performance with different Ge fractions are simulated and analyzed by employing SILVACO TCAD tools. The simulation results show that the high frequency performance of the device can be significantly improved by applying an additional uniaxial stress in the collector. Taking the uniform SiGe base case with the Ge fraction of 0.25 as an example, when y = 0.15, the peak values of fT and fmax reach about 507.7 GHz and 730.7 GHz, respectively. Compared with the SiGe HBT without any additional stress in the collector, f T and f max are respectively increased by 29.1% and 71.5%. When y = 0.1, the proposed device has the best frequency characteristics with the maximum of f T ×f max , and the Johnson's limit (f T ×BV CEO ) is increased by about 26%.